1987
DOI: 10.1007/bf01296029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastrointestinal pH in cystic fibrosis and healthy subjects

Abstract: The primary objective of this study was to define the pH conditions under which supplemental pancreatic enzyme preparations must function in the upper gastrointestinal tract. The hypothesis was that normal or greater acid output in patients with cystic fibrosis (CF), combined with low pancreatic bicarbonate output, results in an acidic duodenal pH, compromising both dosage-form performance and enzyme activity. Gastrointestinal pH profiles were obtained in 10 CF and 10 healthy volunteers under fasting and postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…Moreover, it helps confirm the findings of Youngberg et al published in the journal in 1987. At that time, Youngberg et al showed delayed attainment of pH 5.5 or pH 6.0 in CF subjects compared with healthy controls [3]. Also since this study was performed prior to the availability of proton pump inhibitors (PPIs), the qualitative similarity of the data to that of Gelfond et al supports the present studies assessment that PPI discontinuation in the CF subjects did not materially affect the data.…”
supporting
confidence: 76%
“…Moreover, it helps confirm the findings of Youngberg et al published in the journal in 1987. At that time, Youngberg et al showed delayed attainment of pH 5.5 or pH 6.0 in CF subjects compared with healthy controls [3]. Also since this study was performed prior to the availability of proton pump inhibitors (PPIs), the qualitative similarity of the data to that of Gelfond et al supports the present studies assessment that PPI discontinuation in the CF subjects did not materially affect the data.…”
supporting
confidence: 76%
“…These data indicate that a brief period of elevated duodenal pH occurs upon ingestion of the meal that can be attributed to the cephalic phase of pancreatic bicarbonate secretion. 194 When considered in an overall context, the pH in the postprandial phase in the duodenum is lower than that in the fasted state.…”
Section: The Effect Of Ph On Drug Absorptionmentioning
confidence: 98%
“…Hoogeveen et al [51] demonstrated two CFTR-candidate proteins of 155 and 195 kDa, respectively. In the small intestinal enterocytes, the 155 kDa protein is predominantly localised in the rough endoplasmic reticulum membrane of the mucus secreting cells.…”
Section: The Acid Duodenal Environmentmentioning
confidence: 98%
“…No significant differences in basal or postmilk responses of plasma gastrin could be detected [1]. Continuous radiotelemetric monitoring of duodenal pH shows that postprandial duodenal pH is lower in CF than in healthy subjects [51].…”
Section: The Acid Duodenal Environmentmentioning
confidence: 99%